2020
DOI: 10.3390/rel11040177
|View full text |Cite
|
Sign up to set email alerts
|

Faith Manifest: Spiritual and Mindfulness Tourism in Chiang Mai, Thailand

Abstract: From books to movies, the media is now flush with spiritual and wellness tourist-related images, films, and fiction (which are primarily produced in the West) about Southeast Asia. Combined with the positive effects of spiritual practices, greater numbers of tourists are travelling to Southeast Asia for mindfulness, yoga, and other spiritual pursuits. Influenced by popular mass media coverage, such as Hollywood movies and literary bestsellers like Eat Pray Love (2006) and tourism imaginaries about particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 62 publications
0
10
0
1
Order By: Relevance
“…These tourists are seeking happiness and well-being through such spiritual experiences at yoga and mindfulness centres in Southeast Asia or healing methods that are based on their freely chosen quest instead of any religious obligation (Griffin and Raj, 2017). Choe and O'Regan (2020) explored the motives of western tourists travelling to Chiang Mai in Thailand to engage in mindfulness practices. They concluded that spiritual tourists mainly travelled for problem-solving, well-being intervention, spiritual fulfilment and its transformative potential.…”
Section: Spiritualmentioning
confidence: 99%
“…These tourists are seeking happiness and well-being through such spiritual experiences at yoga and mindfulness centres in Southeast Asia or healing methods that are based on their freely chosen quest instead of any religious obligation (Griffin and Raj, 2017). Choe and O'Regan (2020) explored the motives of western tourists travelling to Chiang Mai in Thailand to engage in mindfulness practices. They concluded that spiritual tourists mainly travelled for problem-solving, well-being intervention, spiritual fulfilment and its transformative potential.…”
Section: Spiritualmentioning
confidence: 99%
“…However, the numbers of those seeking solace and spiritual enlightenment by visiting the sacred sites of other religions and faiths is increasing considerably in what is known as spiritual tourism (Norman, 2011;Timothy & Olsen, 2006). As seekers of spiritual growth and peace, they focus on techniques and methods such as meditation, yoga and chanting (Choe, 2020;Sharpley, 2009). They often find such activities in sacred places that offer religious and cultural experiences different from their own religious faiths.…”
Section: Origin -The Need For Religiously Oriented Travelmentioning
confidence: 99%
“…Religious sites are increasingly being used for enhancing the holistic experiences of body, mind and soul (Choe, 2020;Moufakkira & Selmib, 2018). Due to their location around natural formations of mountains, rivers and valleys, many sites are emerging as popular destinations where religious meets nature and adventure, where religious meets culture, where religious meets spiritual and where religious becomes a way of life for those seeking such experiences.…”
Section: The Next Stops On the Journeymentioning
confidence: 99%
“…Unfortunately, focus on aesthetical transformation on Ramayana stories of Indonesia-Thailand versions is delimitated to the exploration of formalistic aesthetical value that involves viewpoints of literacy (literary art) and visualization (fine art). Social issues in Thailand have made Thailand cultural conservers give more focuses on cultural aspect of aesthetical transformation, which refers to the acculturation of aesthetical value to Buddhism spiritual practice [3].…”
Section: Introductionmentioning
confidence: 99%